2014
DOI: 10.1161/jaha.113.000394
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Death in Heart Disease is Associated With Elevated Urinary Globotriaosylceramide

Abstract: BackgroundElevated urinary globotriaosylceramide (Gb3) has been considered a hallmark of Fabry disease, an X‐linked lysosomal disorder that is a risk factor for most types of heart disease.Methods and ResultsWe screened 1421 consecutive patients with common forms of heart disease for Fabry disease by measuring urinary Gb3 in whole urine using tandem mass spectrometry, α‐galactosidase A activity in dried blood spots, and we looked for GLA mutations by parallel sequencing of the whole gene (exons and introns) in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 44 publications
(79 reference statements)
0
20
0
2
Order By: Relevance
“…30,31 On the other hand, our study demonstrates that analysis of enzyme activity or the amount of substrate in the urine alone lacks the required specificity for large-scale screening. Urinary Gb 3 was elevated in about 15% of patients with heart disease who otherwise did not have GLA mutations, 20 and it is known to be normal in patients with mild mutations and in females, 29 or is falsely elevated for other reasons. 32 α-Galactosidase A activity was not a useful measurement either, because females often have normal enzyme levels 33 and a substantial number (15) of males screened had enzyme activity near or below 2 μmol/L/hr (data not shown), a threshold found to contain patients with Fabry disease.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…30,31 On the other hand, our study demonstrates that analysis of enzyme activity or the amount of substrate in the urine alone lacks the required specificity for large-scale screening. Urinary Gb 3 was elevated in about 15% of patients with heart disease who otherwise did not have GLA mutations, 20 and it is known to be normal in patients with mild mutations and in females, 29 or is falsely elevated for other reasons. 32 α-Galactosidase A activity was not a useful measurement either, because females often have normal enzyme levels 33 and a substantial number (15) of males screened had enzyme activity near or below 2 μmol/L/hr (data not shown), a threshold found to contain patients with Fabry disease.…”
Section: Discussionmentioning
confidence: 99%
“…20 α-Galactosidase A activity evaluation by tandem mass spectrometry Enzyme analysis was performed as previously described. 20 GLA gene analysis GLA gene variants were searched for in pooled DNA using massively parallel sequencing 21 or in individual genomic DNA samples using the Illumina MiSeq platform (Illumina, Inc.; San Diego, CA).…”
Section: Urinary Gb 3 Analysis By Mass Spectrometrymentioning
confidence: 99%
See 1 more Smart Citation
“…38 Despite this, screening for FD using urinary GL-3 levels is not recommended because these markers have been shown to be increased in patients who do not have FD but have common forms of heart disease, such as coronary artery disease or valvular dysfunction. 43 An FD screening study of patients with stroke reported biologically significant Fabry mutations in 21 male (4.9%) and 7 (2.4%) female patients with stroke, 32 but did not publish details on the type of mutations identified. This study could, therefore, have included intronic mutations and other mutations of undetermined clinical significance.…”
Section: Prevalence Of Fd In Patients With Ischemic Strokementioning
confidence: 99%
“…First, 'urinary Gb3 (in the range of classical males)', measured in whole urine, was suggested to confirm FD nephropathy. Others suggested that urinary and/or plasma Gb3 levels may be significantly increased in other diseases than FD [24,25]. Consequently, there was no agreement, although 4/11 of the panelists were convinced that this criterion, in the context of chronic kidney disease and a GLA variant, is sufficient to confirm FD nephropathy.…”
Section: Gold Standardmentioning
confidence: 99%